From "science as measurement" to "measurement and theory": the Cowles Commission and contrasting empirical methodologies at the University of Chicago, 1943 to 1955. Issue 6 (2nd November 2021) - Dimand, Robert W.; Rivot, Sylvie
Abstract: While located at the University of Chicago, the Cowles Commission for Research in Economics advanced a distinctive "Cowles Commission approach" to macroeconomic modelling, using maximum likelihood methods to estimate structurally-identified Keynesian simultaneous-equations models, with the methods presented in two Cowles monographs edited or co-edited by Tjalling Koopmans, a pioneering implementation in another Cowles monograph by Lawrence Klein, and a polemical contrast with the earlier NBER approach in Koopmans's "Measurement Without Theory" critique of Arthur Burns and Wesley Mitchell. The Cowles approach to empirical methodology was vigorously contested at the University of Chicago by Milton Friedman (a former student of Burns and Mitchell), notably in Cowles seminars, in a defence of "Wesley Mitchell as an Economic Theorist" and at a 1949 NBER conference on business cycles. This paper examines the two contrasting approaches to empirical economics at the University of Chicago in the late 1940s and early 1950s, at the confrontations and exchanges between the two approaches, which contributed to the 1955 move of Cowles from Chicago to Yale.